LGBT+ Training Needs for Health and Social Care Professionals: A Cross-cultural Comparison Among Seven European Countries - Baiocco, Roberto; Pezzella, Alfonso; Pistella, Jessica; Kouta, Christiana; Rousou, Elena; Rocamora-Perez, Patricia; López-Liria, Remedios; Dudau, Victor; Doru, Ana Maria; Kuckert-Wöstheinrich, Andrea; Ziegler, Sabine; Nielsen, Dorthe; et al. (My University, 2021)
Introduction: Research suggests that specific training on LGBT+ issues may improve the competencies and skills of health and social care (HSC) professionals, which reduces the negative attitudes toward LGBT+ people. Despite this, there seems to be a lack of coverage of LGBT+ needs in HSC education. The present study aims to explore the specific LGBT+ training needs of HSC professionals and to examine the relationship between these training needs and the four dimensions of the Papadopoulos model, i.e. cultural awareness, cultural knowledge, cultural sensitivity, and cultural competence. Methods: The research used data from a cross-cultural project, “Intercultural Education for Nurses in Europe (IENE9),” which was administered to 412 HSC academics and workers (62% females; Mage = 46.06, SDage = 10.48) between February 2020 and July 2020, in seven European countries: UK (coordinator), Denmark, Spain, Germany, Cyprus, Italy, and Romania. Results: Hierarchical multiple regression showed that higher training needs were associated with cultural awareness, cultural knowledge, and cultural competence. The need for training on LGBT+ issues was higher for Cyprus, Romania, Spain, Italy, and the UK, compared with Denmark (no differences between Germany and Denmark were found). Conclusions: We believe that there has been a lack of focus on the LGBT+ training needs of HSC professionals: Greater efforts are required to develop a culturally competent and compassionate LGBT+ curriculum. Social Policy Implications: Findings from the present study will inform the development of a free, Massive Open Online Course (MOOC), for culturally competent and compassionate HSC professionals in Europe to improve the quality of their care.
Keywords: Training needs; LGBT+; Compassionate curriculum; Negative attitudes; Discrimination; Health and social care professionals